EP276 Toxicity evaluation of locally advanced cervical cancer. (1st November 2019) - da Silva Dias, D; Gosalbez, B; Alves, L; Luz, P; Madureira, T; Vieira, G; Furtado, I
Abstract : Introduction/Background: Cervical cancer represents 6% of gynecological malignant tumors. The incidence in Portugal is 8, 9/100.000, although it is higher in southern region. Concurrent Chemo-radiotherapy (CCRT) is the cornerstone treatment. Methodology: Retrospective analysis of 109 patients diagnosed with locally advanced cervical cancer in our center between 2010 and 2017. The goal is assessing the efficacy of CCRT overall survival (OS), disease-free survival (DFS) and incidence of toxicity. Results: 109 patients, with median age 56 years old. Mostly admitted through emergency department (79%), being the most common symptom metrorrhagia (46, 8%). 65, 1% were Stage IIB. Median time from diagnosis to multidisciplinary committee (MC) was 47 days and from MC to beginning of CCRT was 21 days. CCRT was initiated in 87 (79, 8%) patients. DFS was 63% and OS 64% at 5 years. From 522 chemotherapy sessions, only 9 presented severe toxicities, especially haematological grade 3. No relation with OS or DFS was found. 46% (n=40) presented radiotherapy toxicity, especially chronic (n=31). Proctitis (n=24) was the most prevalent. A change was observed in 2015, patients diagnosed before presented an alarming 36, 7% of proctitis versus 20% after 2015. A significant difference was observed between radiotherapy toxicity and OS (p=0, 018), especially fistulas and proctitis. Median radiation dose was 73Gy. A positive correlation was observed in the incidence of toxicity when exposed to doses ≥75 Gy (p=0, 007; HR 4, 73 [95% CI: 1, 52–14, 71]), especially diarrhea and proctitis. Conclusion: The OS and DFS are in concordance with results around European countries. A high incidence of radiation toxicity was evident, although an improvement was observed since 2015. Our radiation clinic has an intensity-modulated radiation therapy (IMRT) since 2018 and we are eager to evaluate the effect in toxicity in the years to come. Disclosure: Nothing to disclose.